PENGARUH TRAINING & DEVELOPMENT, MOTIVASI TERHADAP PRESTASI KERJA KARYAWAN PADA PT PLN PERSERO KABUPATEN SIJUNJUNG - Andrizal, Andrizal; Kemala Sari, SE, MM, Mareta; Natassia, SE, MM, Rizky (Pendidikan Ekonomi, 2014)
ABSTRACTThis research was conducted in the District Sijunjung regarding training & development , motivation on employee performance at PT . PLN Persero Sijunjung district . The purpose of this study was to obtain evidence of the effect of training & development , motivation on employee performance in PT . PLN Persero Sijunjung district .The method used in this research is descriptive and associative . This research is a field , where the use of secondary data . Training & development ( X1 ) , motivation ( X2 ) and job performance ( Y ) is obtained from documentation PT . PLN Persero Sijunjung district . Analysis of the data used in this study is a descriptive analysis and inductive analysis which consists of classical assumption test , multiple linear regression analysis and hypothesis testing .Based on multiple linear regression equation it can be seen that the regression coefficient of training & development ( X1 ) obtained a value of 0.366 with a positive coefficient sign ( + ) , motivation ( X2 ) obtained a value of 0.156 . This means that the training & development , motivation can increase job performance in PT . PLN Persero Sijunjung . Significance value of the variable value of the training and development of 0.000 < 0.05 , and the value of the variable motivational significance of 0.043 < 0.05 It can be concluded that the training & development , motivation jointly affect performance in PT . PLN Persero Sijunjung district .Based on these results , it is suggested that employees of PT . PLN Persero Sijunjung district to be more active in running training & development , and motivation of employees so that performance can be increased .Keywords : Training & Development and Motivation , Job Performance